Phenomenological Study: Guidance and Counseling Teachers' Experiences in Developing Grit in Dyslexic Children at the Talenta Perdagangan Special Needs School - Azmi, Fadia Nurul; Darmayanti, Nefi; Abdurrahman, Abdurrahman (FKIP - Universitas Riau, 2025)
This study aims to analyze the experiences of guidance and counseling teachers in developing grit in children with dyslexia at Talenta Dagang SLB. The research methodology used was qualitative, with a phenomenological approach. The data collection strategy employed in-depth interviews with a semi-structured interview guide. Data analysis used Interpretative Phenomenological Analysis (IPA), and three themes emerged: (1) Experiences of children with dyslexia in overcoming learning difficulties, (2) The role of guidance and counseling teachers in developing grit in children with dyslexia, and (3) Inhibiting factors in developing grit in children with dyslexia. The results showed that children with dyslexia initially experienced frustration, laziness, and hopelessness due to repeated failures in reading, writing, and spelling, as well as social pressure from comparison with peers. However, through guidance from guidance counselors, family support, and small achievements that foster a sense of pride, children begin to become more patient, braver in trying, and more enthusiastic about learning despite still facing obstacles. Parental involvement facilitated by guidance counselors also strengthens the consistency of support for children. The development of grit in dyslexic children at Talenta Dagang Special School is hampered by various interrelated factors, including psychological, cognitive, social, structural, and learning facilities.